Current Projects - Alice Aycock (Oz, 2000)
The portfolio of works shown in the following pages are computer visualizations in form-Z. None of the work exists in reality although several will be built in next few years. Ed. note: Designs for 5 sculptural projects by sculptor Alice Aycock. University of South Florida, Tampa; South Gate, Miami Heat Arena, Miami; George H. Fallon Office Building, Baltimore; Waterworks Proposal for McWane Center Plaza, Birmingham, AL; Sculpture, “The Unconsciousness of the Landscape Becomes Complete,” Rowan University, Glassboro, NJ.